Work-related learning and professional growth of students at a selected open university in Zimbabwe - Rajlal, Ashnee; Muchowe, Regis Misheal; Chitamba, Anos (Edelweiss Applied Science and Technology, 2025)
This study examines the relationship between work-related learning (WRL) and the professional development of students at Zimbabwe Open University. The purpose of the research, guided by Experiential Learning Theory, is to identify how WRL influences students’ employability, problem-solving abilities, and entrepreneurial skills. Using a quantitative approach, data were collected through a structured questionnaire administered to 148 third-year Commerce students. The data were analyzed using both descriptive and inferential statistical methods. Findings suggest that WRL significantly improves students’ problem-solving skills and employability. Conversely, a notable negative correlation was observed between WRL and the development of entrepreneurial skills, indicating that structured workplace environments may limit creativity. Students also reported facing challenges related to mentorship and the alignment between academic learning and industry expectations. The study concludes that while WRL is essential for preparing students for the workforce, its design should be optimized to support more comprehensive professional development. It is recommended that universities and industry partners strengthen collaboration by integrating structured mentorship programs, aligning curricula more closely with industry requirements, and intentionally promoting entrepreneurial skill development within WRL initiatives.